Phuket mascot design from based on cultural value - Jirawat Sookkaew; Nakarin Chaikaew; Pipatpong Saephoo (Institute of Advanced Engineering and Science, 2023)
Designing with cultural, wisdom, way of life, beliefs, and other values that have been passed down through generations. Let's produce a creative product that is entertaining and varied. One of them is to design a mascot to be used in the media as a character and representation of something, and to imply that this mascot will be able to act on behalf of those representatives. It is clear that Phuket has an exceptional and valuable cultural capital. In addition, there are numerous traditions, rituals, beliefs, customs, arts, and civilizations that are indigenous to the local population. It was thought that this study did a good job of figuring out how to use cultural values to make characters by applying design theory or design science to creativity. It also did a good job of figuring out how applicable the methods and design approaches were.